Detection of Mycobacterium avium subspecies paratuberculosis in formula milk from Bogor using PCR IS 900 (Medical Journal of Indonesia, 2008)
Crohn's disease (CD) that becomes a public health concern in developed countries shows similarities in clinical signs and pathological features with Johne's disease (JD) in ruminants infected by Mycobacterium avium subspecies paratuberculosis (MAP). Few researches conducted in Europe, the USA, and Australia showed relationships between MAP, CD, JD and dairy products. Indonesians consume milk and diary products from domestic and imported source. Adji in 2004 found some domestic dairy cows that were seropositive for MAP, and this could be a serious problem in dairy farm animals and human health in the future. The aim of this study was to detect MAP in the growing up formula milk. Fifty samples from five established factories were taken from supermarkets in Bogor. Polymerase chain reaction method (PCR) with insertion sequence (IS) 900 as primer and culture in Herrold's egg yolk media with mycobactin J (HEYM J) as a gold standard were used in this study. Neither MAP grew up in HEYM J medium after 20 weeks of culture period nor positive samples by PCR IS 900 were found. Although there were no positive samples found in this study, further extensive and comprehensive studies on MAP should be done with more and varied samples, as well as in human to provide data on MAP in Indonesia. (Med J Indones 2008; 17: 183-7)